Have euro area and EU economic governance worked? Just the facts - Demosthenes Ioannou; Livio Stracca (European Central Bank (ECB), 2011)
We test whether two key elements of the EU and euro area economic governance framework, the Stability and Growth Pact and the Lisbon Strategy, have had any impact on macroeconomic outcomes. We test this proposition using a difference-in-difference approach on a panel of over 30 countries, some of which are non-EU (control group). Hence, the impact of the EU economic governance pillars is evaluated based on both the performance before and after their application as well as against the control group. We find strong and robust evidence that neither the Stability and Growth Pact nor the Lisbon Strategy have had a significant beneficial impact on fiscal and economic performance outcomes. We conclude that a profound reform of these pillars is needed to make them work in the next decade.
Keywords: E62; E63; H63; O43; 330; euro area; European Union; governance; institutions; Lisbon Strategy; Stability and Growth Pact